Consumption of aphrodisiac drugs without prescription among men in Saudi Arabia: cross-sectional study - Sameer Hamdy Hafez; Sadeq Abdo Mohammed Alwesabi; Elwaleed Idris Sagiron; Hanan Saad Abdullah Alwadei; Abdalla MohamedAhmed Osman Abdalla; Elsadig Eltaher Hamed ِAbdulrahman; Nahid Khalil Elfaki; Noha Ahmed Mohamed; Mohammed Abdulrahman Alshahrani; Ahmad A. Alshehri; Mohammed Jamaan Alzahrani; Amna Mohammed Idris; et al. (Elsevier, 2024)
Background: The prevalence and patterns of aphrodisiac drug consumption without prescription among men in Saudi Arabia remain underexplored, with limited empirical evidence available. Given the potential health implications and societal considerations, a comprehensive investigation is warranted. Aim: Assess the Prevalence, pattern of use and the associated factors of Aphrodisiac drugs consumption without prescription among men at Najran City, Saudi Arabia. Methods: Employing a cross-sectional descriptive study, 500 participants were included through convenience sampling. The utilized questionnaires covered a range of data, including socio-demographic information, patterns of aphrodisiac use, knowledge about aphrodisiacs, lifestyle details, a sexual health inventory for men, and a perceived stress level scale. Results: The study reveals a significant prevalence of unsanctioned aphrodisiac drug use (31%) among men in Najran City, Saudi Arabia, with a majority (79.3%) consuming these substances four times monthly. Associated disparities in knowledge, lifestyle, stress, and sexual function underscore the urgent need for policy interventions and tailored health education initiatives for this demographic. Conclusion: Approximately one-third of the sampled population engaged in the unsanctioned use of aphrodisiac drugs, with the majority utilizing them four times monthly. Tablets emerged as the most prevalent form of consumption. Commonly cited motives and justifications included peer influence and the perceived safety of aphrodisiacs. Influential factors encompassed levels of knowledge, lifestyle, stress levels, erectile function, age, education, and the number of wives. Recommendations: Urgent policy interventions are warranted to regulate the acquisition and distribution of aphrodisiacs. Tailored health education initiatives should be implemented for married and prospective married men.